Activating sacred objects in public space: Bernini's angels on the Ponte Sant'Angelo in early modern Rome - Whitford, Kelly (Material religion, 2018)
In 1667, Pope Clement IX commissioned Gian Lorenzo Bernini to design 10 sculptures of angels to decorate the Ponte Sant'Angelo in Rome. Contemporary accounts record that the faithful experienced Bernini's statues as animated celestial figures at the heart of the city. The ability of the marble angels to persuasively move beholders fulfilled the aims of the papal commission to expand the reach of the Church into the urban space of Rome. This paper examines how these religious objects were activated in a public space, a setting composed of sacred and profane elements. In the early modern era, the Ponte Sant'Angelo connected Rome's city center to St. Peter's Basilica while also serving as a setting for civic processions, spectacular fireworks displays, and public executions. While angels were ubiquitous in the city's sacred spaces, like church interiors, Bernini's sculptures materialized a flock of angels at an outdoor, urban nexus of theology, spectacle, and justice. Drawing on theories of performance that conceptualize the profound religious encounter that can result from the simultaneous juxtaposition of sacred and profane elements, this paper argues that the public setting activated Bernini's marble statues so that they were experienced as lively celestial figures by the faithful.